Redefining Malay Food in the Post Malaysia's New Economic Policy (NEP) / Abd. Razak Aziz and Awang Azaman Awang Pawi - Aziz, Abd. Razak; Awang Pawi, Awang Azaman (UiTM Press, 2016)
The Malays whom many were from the rural areas have moved up the hierarchical class ladder in the past ten to twenty years, joining the middle class and are much expose to a more contemporary food items. Moreover, the heavy influence of diversity of regional and other ethnics' cuisine and the plethora of ingredients have produced a cuisine which is completely changed from its predecessor. In addition, Malay cuisine is still struggling to position itself locally and internationally. In term of research, there had been attempts but many failed in understanding the nature of Malay food. Therefore, consumers are unable differentiate between a Malay food and others due to the lack of a apparent identity. As a result, young Malay Chefs have begun to reinterpret, rejuvenate, invents or reinvents, borrow or exchange specific food and foodways of another ethnic group in assigning a decent position to the Malay food identity. This study adopted the qualitative method in assessing the complex social phenomena of Malay food preparation and consumption behavior.